Anti-Inflammatory Activity and Chemical Profile of Galphimia glauca - González-Cortazar, Manasés; Herrera-Ruiz, Maribel; Zamilpa, Alejandro; Jiménez-Ferrer, Enrique; Marquina, Silvia; Álvarez, Laura; Tortoriello, Jaime (Planta Medica, 2014)
Galphimia glauca, commonly known as “flor de estrella”, is a plant species used in Mexican traditional medicine for the treatment of different diseases that have an acute or chronic inflammatory process in common. Aerial parts of this plant contain nor-seco-triterpenoids with anxiolytic properties, which have been denominated galphimines. Other compounds identified in the plant are tetragalloyl-quinic acid, gallic acid, and quercetin, which are able to inhibit the bronchial obstruction induced by platelet-activating factor. The objective of this work was to evaluate the anti-inflammatory effect of crude extracts from G. glauca and, by means of bioguided chemical separation, to identify the compounds responsible for this pharmacological activity. n-Hexane, ethyl acetate, dichloromethane, and methanol extracts showed an important anti-inflammatory effect. Chemical separation of the active methanol extract allowed us to identify the nor-seco-triterpenes galphimine-A (1) and galphimine-E (3) as the anti-inflammatory principles. Analysis of structure-activity relationships evidenced that the presence of an oxygenated function in C6 is absolutely necessary to show activity. In this work, the isolation and structural elucidation of two new nor-seco-triterpenes denominated as galphimine-K (4) and galphimine-L (5), together with different alkanes, fatty acids, as well as three flavonoids (17–19), are described, to our knowledge for the first time, from Galphimia glauca.
Keywords: Galphimia glauca; Malpighiaceae; galphimine; nor-secotriterpene; anti-inflammatory activity; flavonoid; organic acids